The Strengths and Difficulties Questionnaire (SDQ): Factor Structure and Gender Equivalence in Norwegian Adolescents. - Tormod Bøe; Mari Hysing; Jens Christoffer Skogen; Kyrre Breivik (PLoS ONE, 2016)
Although frequently used with older adolescents, few studies of the factor structure, internal consistency and gender equivalence of the SDQ exists for this age group, with inconsistent findings. In the present study, confirmatory factor analysis (CFA) was used to evaluate the five-factor structure of the SDQ in a population sample of 10,254 16-18 year-olds from the youth@hordaland study. Measurement invariance across gender was assessed using multigroup CFA. A modestly modified five-factor solution fitted the data acceptably, accounting for one cross loading and some local dependencies. Importantly, partial measurement non-invariance was identified, with differential item functioning in eight items, and higher correlations between emotional and conduct problems for boys compared to girls. Implications for use clinically and in research are discussed.